An upstream open reading frame (uORF) signals for cellular localization of the virulence factor implicated in pregnancy associated malaria. Issue 10 (15th March 2018) - Fastman, Yair; Assaraf, Shany; Rose, Miriam; Milrot, Elad; Basore, Katherine; Arasu, B Sivanandam; Desai, Sanjay A; Elbaum, Michael; Dzikowski, Ron
Abstract: Plasmodium falciparum, the causative agent of the deadliest form of human malaria, alternates expression of variable antigens, encoded by members of a multi-copy gene family named var . In var2csa, the var gene implicated in pregnancy-associated malaria, translational repression is regulated by a unique upstream open reading frame (uORF) found only in its 5′ UTR. Here, we report that this translated uORF significantly alters both transcription and posttranslational protein trafficking. The parasite can alter a protein's destination without any modifications to the protein itself, but instead by an element within the 5′ UTR of the transcript. This uORF-dependent localization was confirmed by single molecule STORM imaging, followed by fusion of the uORF to a reporter gene which changes its cellular localization from cytoplasmic to ER-associated. These data point towards a novel regulatory role of uORF in protein trafficking, with important implications for the pathology of pregnancy-associated malaria.